Evaluation of the Sensory Quality and Shelf Life of a Bioactive Essence Rich in Monounsaturated Fatty Acids and Antioxidants, Obtained from Eco-Sustainable Iberian Ham - Eva Bruna-García; Marta Miguel-Castro; Beatriz Isabel-Redondo (Foods)
Food sustainability through traditional food production and the reuse of food by-products is one of the characteristics most valued by consumers. The production of Iberian ham is linked to the vaporization and sustainability of the dehesa and the conservation and maintenance of the rural environment, but there are some by-products that are not destined for direct consumption. In this context, previous studies have used trimmed fat to obtain a bioactive essence rich in antioxidants and monounsaturated fatty acids. Furthermore, it is important to keep in mind that the consumer’s decision is influenced by the nutritional/health and sensory characteristics of the product and its shelf life. The objective of the present study was to evaluate consumer acceptance and/or preference of different essences obtained from the trimmed fat of sliced Iberian ham and to determine the microbiological and physicochemical stability of the selected sustainable essence over time. The results showed that this essence is generally accepted by consumers and is microbiologically stable over time.